As-Sīmiyāiyah Li Ferdinand De Saussure Fī Riwāyah ‘Asākir Qous Quzh Li Andrea Hirata (Al-Qiyam al-Islāmiyah Anmudzajan) - Riyadi, Agus; Bahri, Samsul; Parida, Hasna; Azhari, Faiz (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
In the novel "Laskar Pelangi (Asakir Qous Quzh)" by Andrea Hirata, it was said that on the island of Belitung Ekal and his nine companions were students in the Muhammadiyah elementary school. Without knowing from this novel, Islamic values were obtained for the readers using semiotics at Ferdinand de Saussure from his structural theory that contains the sign, the signifier, and the signified. This research aims to stand on the forms of semiotics and Islamic values in the novel "Laskar Pelangi (Asakir Qous Quzh)" by Andrea Hirata in the theory of semiotics of Ferdinand de Saussure. This research is a type of qualitative desk research, and the researcher used the method of collecting data in this research using the method of documents. The researcher used the descriptive approach and the analytical graphic approach to analyze the data obtained from the quotations of the novel in this research. The research concludes that the forms of semiotics in the novel Soldiers of the Rainbow are 43 forms of the signifier and the signified in the 43 quotations from the conversations therein. and 24 Islamic values in 43 quotes from 80 conversations. This research has many implications. This will expand our understanding of the linguistic and non-linguistic aspects that authors use to create meaning in literary works, providing insight into how authors use Islamic values as a source of inspiration in constructing narratives and communicating deeper values to readers, and revealing how Islamic values influence the signifiers used by the author. And how to convey Islamic values through the signs in the novel. This research will make an important contribution to understanding the relationship between semiotic analysis and Islamic values and meaning in literary works.